Pemanfaatan Media Pembelajaran Berbasis AI Untuk Meningkatkan Minat Belajar Siswa SD Negeri 060972 Simalingkar B Medan - Baringbing, Elsinta Karolina Br; Rahim, Robbi (LPPM STIKOM Tunas Bangsa, 2024)
The development of time and technology has brought significant progress in the world of education, including the use of AI-based learning media. Many schools are now using technology to facilitate the teaching and learning process, help teachers improve student achievement, and attract learners. This qualitative research uses content analysis to evaluate the use of AI learning media at SD Negeri 060972 Medan. The results show that AI-based learning media is effective in increasing students' interest in learning science subjects in class III. However, the obstacle faced is the lack of available learning media, which hampers teachers' creativity in the learning process